2002
DOI: 10.1063/1.1425077
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption and photoluminescence studies on CdS quantum dots in Nafion

Abstract: Excitonic effects are observed in the optical absorption and photoluminescence of strongly confined CdS quantum dots embedded in the polymer Nafion. The three bands identified in the optical absorption spectra could be attributed to 1s e -1s h , 1p e -1p h , and 2s e -2s h transitions of the noninteracting particle model. Photoluminescence spectra show a strong emission band corresponding to electron-hole recombination and a weak band due to emission from defect states. The strength of electron-phonon coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 17 publications
2
34
1
Order By: Relevance
“…The cadmium vacancies and interstitial sulfur act as acceptors, while sulfur vacancies and interstitial cadmium act as donors. There are several reports [44,45] on the study of room-temperature PL spectra of CdS nanoparticles. The green, yellow and red emissions in CdS nanoparticles have also been studied in detail [46].…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…The cadmium vacancies and interstitial sulfur act as acceptors, while sulfur vacancies and interstitial cadmium act as donors. There are several reports [44,45] on the study of room-temperature PL spectra of CdS nanoparticles. The green, yellow and red emissions in CdS nanoparticles have also been studied in detail [46].…”
Section: Photoluminescence Spectroscopymentioning
confidence: 99%
“…Quantum dots based on GaN [4], ZnSe [5], ZnO [6], MgO [7], CuCl [8] and CdS [9] have been fabricated and their properties are studied in considerable detail. It has been suggested that the lasing mechanism in these systems is excitonic in nature and therefore can lead to lower values of the threshold current densities.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] This interest is stimulated by remarkably different optical properties when semiconductor sizes are decreased from bulk to a few nanometers as predicted by quantum confinement theory.…”
Section: Introductionmentioning
confidence: 99%